PRINSIP PRINSIP GOOD GOVERNANCE TRANSPARANSI DAN AKUNTABILITAS PADA KPP PRATAMA CIKARANG UTARA - Puspasari, Aprilia (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2019)
Multi-dimensional crisis in Indonesia, among others, one of which is caused by procedures of governance that is not properly managed and regulated. Consequently arise various problems such as corruption, collusion and nepotism (KKN). Good governance (good governance) is a conception of clean governance, democratic, effective and appropriate contribution, empowerment, and the balance between the three pillars (government, private businesses ,and communities). Governmental organizations should be able to compete with private businesses in managing their resources, so that the necessary preparedness of government agencies to implement good governance such as accountability and transparency. The research method used in this journal analyze the effect of transparency and accountability for that is part of the principles of good governance, research analysis techniques include test validity is a stage where the gauges can measure what should be measured, so that a study using the questionnaire as its validity needs to be tested empirically. Reliability test is performed to measure the consistency of constructs or variables. A questionnaire said reliable or reliable if a person answers to the statement are consistent or stable over time. Normality test data is performed to determine whether the data were normally distributed or not. And regression test to see the relationship of the independent variables and the dependent variable significantly. Statistical analyzes were performed showing the discovery: the correlations table looks great with the accountability relationships between variables were calculated with the transparency of the correlation coefficient is 0.073,  Theoretically,  the variable transparency has no effect on accountability.